Requirements for Eliciting a Spastic Response With Passive Joint Movements and the Influence of Velocity on Response Patterns: An Experimental Study of Velocity-Response Relationships in Mild Spasticity With Repeated-Measures Analysis - Fujimura, Kenta; Mukaino, Masahiko; Itoh, Shota; Miwa, Haruna; Itoh, Ryoka; Narukawa, Daisuke; Tanikawa, Hiroki; Kanada, Yoshikiyo; Saitoh, Eiichi; Otaka, Yohei (Frontiers in Neurology, 2022)
Background Spasticity is defined as a velocity-dependent increase in tonic stretch reflexes and is manually assessed in clinical practice. However, the best method for the clinical assessment of spasticity has not been objectively described. This study analyzed the clinical procedure to assess spasticity of the elbow joint using an electrogoniometer and investigated the appropriate velocity required to elicit a spastic response and the influence of velocity on the kinematic response pattern. Methods This study included eight healthy individuals and 15 patients with spasticity who scored 1 or 1+ on the modified Ashworth Scale (MAS). Examiners were instructed to manually assess spasticity twice at two different velocities (slow and fast velocity conditions). During the assessment, velocity, deceleration value, and angle [described as the % range of motion (%ROM)] at the moment of resistance were measured using an electrogoniometer. Differences between the slow and fast conditions were evaluated. In addition, variations among the fast condition such as the responses against passive elbow extension at <200, 200–300, 300–400, 400°/s velocities were compared between the MAS 1+, MAS 1, and control groups. Results Significant differences were observed in the angular deceleration value and %ROM in the fast velocity condition (417 ± 80°/s) between patients and healthy individuals, but there was no difference in the slow velocity condition (103 ± 29°/s). In addition, the deceleration values were significantly different between the MAS 1 and MAS 1+ groups in velocity conditions faster than 300°/s. In contrast, the value of %ROM plateaued when the velocity was faster than 200°/s. Conclusion The velocity of the passive motion had a significant effect on the response pattern of the elbow joint. The velocity-response pattern differed between deceleration and the angle at which the catch occurred; the value of deceleration value for passive motion was highly dependent on the velocity, while the %ROM was relatively stable above a certain velocity threshold. These results provide clues for accurate assessment of spasticity in clinical practice.